Comparison between alpha beta pruning algorithm and greedy algorithm in designing winning strategies in the game of checkers / Christy Jr Tan - Jr Tan, Christy (Faculty of Information Technology and Quantitative Sciences, 2007)
Alpha Beta Pruning is an algorithm to prune unnecessary branches. The idea of not exploring the branches if we know that it is worthless makes it a powerful algorithm ever invented. The algorithm is useful in some of the game search available today. Meanwhile, the ability of greedy algorithm to solve problem by choosing any alternatives that leads to the optimal solution without having care of what will happen after that as long as it achieves its goal makes it suitable in any game it applies. Some of the games are checkers. Checkers uses game search to find the solution to win the game. There are many available locations that the pieces can move in the board. It makes it difficult for the player to determine the next move that it should go to win the game. This game will be used to compare both algorithm based on time and the number of moves it takes to win the game. By applying both algorithms, we can determine which algorithm is the most powerful algorithm to generate the winning strategies in the game of checkers. The result will also show how the algorithms generate the winning solution.